The Renaissance of fullerenes with perovskite solar cells. (November 2017) - Gatti, Teresa; Menna, Enzo; Meneghetti, Moreno; Maggini, Michele; Petrozza, Annamaria; Lamberti, Francesco
Abstract: Fullerenes have been extensively used for more than two decades for the development of organic photovoltaics (OPV). While OPV seems to be a technology almost ready for the market, in the last few years fullerenes are attracting a big interest for the improvement they afford on the already well-performing perovskite solar cells (PSCs). Thanks to PSC integration, interest in fullerenes is rising again, opening up new exciting perspectives for photovoltaics. This review article aims at analyzing the landmark contributions that gave birth to the novel application of fullerenes in PSCs and to the technological solutions that are emerging with them. Graphical abstract: Highlights: The use of fullerene as ETL in perovskite solar cells is recent and ground-breaking. The performance of devices is improved, via elimination of electrical hysteresis. Key works that led to this innovation are reviewed and critically analyzed. Emphasis is on functionalized fullerenes to tackle specific challenges.